Facebook and Google care deeply about journalism’? Mapping audience-based monetization projects and the impact on journalistic practices and values - Papa, Venetia; Kouros, Theodoros (My University, 2023)
Facebook and Google launches in 2017 and 2020, ‘Google News Initiative’ and ‘Facebook Journalism Project’ respectively to provide cutting-edge tools to help journalists understand and connect with their users, improve their products and power their technological infrastructure. This goes in line with the strategy of ‘infrastructuralization’ applied by Google and Facebook to centralize international flows and reinvent relationships between diverse publics (Plantin et.al., 2018). Along with this, news organizations have been forced to reinvent the ways by adapting their editorial decisions, shaping their forms in search of alternatives by which they can monetize their news stories through a ‘platform native strategy’. Thus, technological platforms are seen as ‘digital intermediaries’ with specific business models where data-power processes tackle the production, monetization and visibility of journalistic content. While this is evident, publishers and news organizations might reinvigorate their institutional practices and values to priorities and values of the platforms in a process of “institutional isomorphism” (Caplan and Boyd, 2018). Whereas significant empirical and theoretical work has been focused on the promises of technology on journalism per se, little is known about innovation projects that take place within technological corporations and are vastly applied in news organisations. Thus, little is known about human aspects of technological approaches in influencing journalistic identities. This article combines the fields of digital journalism, affordance theory and critical data studies, engaging in a sociotechnical analysis of ‘big techs projects’ to understand the material means by which technological corporations strives to engage journalists vis-à-vis their business models. Empirically, the study draws on two sets of projects (‘Google News Initiative’ and ‘Facebook Journalism Project) to explore the following questions: what kind of ‘tools’ social media platforms provide journalists to harmonize with established power structures and how these tools mediate the practices and news values of journalists? Our aim, is to explore the ways by which ‘big techs’ attempt to engage journalists and render corporate platforms more accessible to them? Regarding the method of analysis, we proceeded in three steps. First, we studied all texts related to the projects’ websites (descriptions, instructions of use, available tools, etc.) and other sources linked to by their websites (e.g. media articles, commentaries, interviews) to get a sense of the projects’ philosophy. Second, to explore the affordances of each project, we performed a discursive interface analysis of the selected cases. Stanfill (2015) explains how discursive interface analysis interprets the assumptions built in websites and applications through the analysis of their affordances, to reveal ‘how norms for technologies and their users are produced and with what implications’ (p. 1059). Based on the premise that ‘the interface of a computing technology is the manifestation of its implicit politics and ideology’ (Sun and Hart-Davidson, 2014: 3534), affordances entail normative claims ‘about what Users should do’ (Stanfill, 2015: 1062) in our case journalists. In this method, affordances are seen as producing discourses, articulating ‘structural ideals that position particular behavior as “correct” or “normal”’ thus ‘reflecting social logics and non-deterministically reinforcing them’ (Stanfill, 2015: 1060). Third, we documented and analysed through thematic content analysis 620 ‘success’ stories of implementation of different tools suggested by: a) Facebook Journalism project (e.g., Breaking News Label, Facebook Watch, Crowd Tangle, Facebook Live) within newsrooms in Africa, Asia-Pacific, Europe, Latin America and North America b) Google News Initiative project (e.g. Monetization, Storytelling, Distribution and Management, Data and Infrastructure) within news rooms around the world. Preliminary findings indicate that data literacies (data identification/data understandings/data uses) are a prerequisite to practice journalism which in turn creates a sort of ‘datafied’ journalistic identities. Similarly, journalists are paying attention to the actions and tools which are encouraged by ‘big tech’ affordances, creating the impression that these tools are technological ‘fixes’ aiming to empower and protect ‘journalists’ in their everyday practices, instead of promoting the quality of their news stories.
Keywords: Digital journalism; Affordance theory; Critical data studies